The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/039463200902200323
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Zirconia-Toughened Alumina: Promising Mechanical Properties and Absence of In Vitro Carcinogenicity

Abstract: High purity alumina as well as zirconia ceramics have been widely used as orthopaedic implant biomaterials and dental devices displaying optimal, but sometimes exclusive, mechanical properties. In order to combine the advantages of alumina and zirconia ceramic materials different types of composites have been developed in which either zirconia is dispersed in an alumina matrix or vice versa. Orthopaedic and dental implant biomaterials are expected to be in contact with living tissues for a long period of time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…In a previous study we reported a new ZTA ceramic obtained within a project aimed to develop new ceramic materials of high strength and toughness suitable for biomedical applications and demonstrated that it did not elicit mutagenic nor carcinogenic effects in vitro (7). The material is currently under consideration for patent and we proposed it as a suitable biomaterial for load bearing applications such as orthopaedic implants or dental devices.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we reported a new ZTA ceramic obtained within a project aimed to develop new ceramic materials of high strength and toughness suitable for biomedical applications and demonstrated that it did not elicit mutagenic nor carcinogenic effects in vitro (7). The material is currently under consideration for patent and we proposed it as a suitable biomaterial for load bearing applications such as orthopaedic implants or dental devices.…”
Section: Discussionmentioning
confidence: 99%
“…Additives such as zirconia are incorporated into alumina matrices to serve as toughening agents. The details of these mechanisms are beyond the scope of this review, but in short, controlled phase transformation of sub-micron zirconia particles within the alumina matrix prevents subcritical crack propagation, resulting in decreased fracture rates (De Aza et al, 2002;Insley et al, 2002;Maccauro et al, 2009). However, these materials have a relatively short clinical history, so further monitoring is necessary.…”
mentioning
confidence: 99%
“…These biocompatibility capabilities are preserved also on binary zirconia-alumina composites, as assessed by Maccauro et al [49]. Their results, based on DNA damage, mutagenicity, and cancerogenetic potential in mammalian cells, confirmed that ZTA material could be considered suitable for biomedical applications.…”
Section: Genotoxicitymentioning
confidence: 71%